Peculiarity of the Cathodoluminescence of lpha- Alumina Prepared by Calcination of Gibbsite Powder or Generated by Oxidation of a Metallic FeCrAl Alloy - Abdelkader, Djelloul; Abdecharif, Boumaza (IntechOpen, 2012)
None